Double-stranded RNA bending by AU-tract sequences. Issue 22 (27th November 2020) - Marin-Gonzalez, Alberto; Aicart-Ramos, Clara; Marin-Baquero, Mikel; Martín-González, Alejandro; Suomalainen, Maarit; Kannan, Abhilash; Vilhena, J G; Greber, Urs F; Moreno-Herrero, Fernando; Pérez, Rubén
Abstract: Sequence-dependent structural deformations of the DNA double helix (dsDNA) have been extensively studied, where adenine tracts (A-tracts) provide a striking example for global bending in the molecule. However, in contrast to dsDNA, sequence-dependent structural features of dsRNA have received little attention. In this work, we demonstrate that the nucleotide sequence can induce a bend in a canonical Watson-Crick base-paired dsRNA helix. Using all-atom molecular dynamics simulations, we identified a sequence motif consisting of alternating adenines and uracils, or AU-tracts, that strongly bend the RNA double-helix. This finding was experimentally validated using atomic force microscopy imaging of dsRNA molecules designed to display macroscopic curvature via repetitions of phased AU-tract motifs. At the atomic level, this novel phenomenon originates from a localized compression of the dsRNA major groove and a large propeller twist at the position of the AU-tract. Moreover, the magnitude of the bending can be modulated by changing the length of the AU-tract. Altogether, our results demonstrate the possibility of modifying the dsRNA curvature by means of its nucleotide sequence, which may be exploited in the emerging field of RNA nanotechnology and might also constitute a natural mechanism for proteins to achieve recognition of specific dsRNA sequences.